Luxury wine in Rome - Aguilera Martín, Antonio (Romanitas - Revista de Estudos Grecolatinos, 2025)
The relationship between humans and food initially arises as a primary response to the stimulus of hunger, as a natural instinct for survival. The oldest civilizations emerged where sustenance was guaranteed, and their evolution is closely connected to advancements in the productive sphere. In archaic Roman society, food consisted of products derived from an agricultural and pastoral economy, but contacts with the Etruscans and Greeks permeated Roman culture with new values: the banquet became associated with pomp and luxury as a tangible and necessarily manifest expression of real wealth; even wine became one of the characteristic and most important elements to demonstrate this social status. The aim of this text is to present how wine, unknown to the Greeks and Romans in the archaic period, became a fundamental food on the Roman table and how the Romans developed specific techniques for the cultivation and production of this beverage. In the second part of this article, I will present the results of an experiment conducted between 2009 and 2013 in which we aimed to verify if a wine considered luxurious by the Romans could be considered a quality wine today.
Keywords: Wine; Rome; Cultivation; Social status